Apology Situations and Emotional Experiences: A Study on Japanese and Turkish University Students - Toksöz, Levent (Border Crossing, 2018)
The purpose of this study is to classify the apology situations that Japanese and Turkish university students often experience in their daily lives, and to clarify their emotional experiences. In the study, 97 Japanese and 61 Turkish university students have been asked about their recent apologies and their feelings while apologizing. As a result of the survey, it has been determined that breach of responsibility (sekimu furiko) and breaking a promise (yakusoku ihan) are the most frequently observed apology situations in Japan. On the other hand, it has been understood that injuring (emotional injuring) is the most frequently observed apology situation in Turkey. In addition, it has been found that regret, feeling of guilt, and sadness are the fundamental emotions in both countries.